A profile of the United States toy industry : serious fun - Byrne, Christopher (Industry profiles collection., 2013)
The toy industry is one of the most consistently misunderstood sectors of American business. That's no surprise because on many levels it resists easy definition. It's a commodity business. No, it's a fashion business. No, it's a consumer products business. No, it's an entertainment business. The fact is it's all of these businesses, each of which addresses and responds to market forces differently. And often, especially with the larger, publicly traded companies -- all of these businesses share a balance sheet. Toy consumers are equally diverse, ranging from grandparents planning a splurge, to parents hoping to give their kids a leg up in learning to kids parting with their pocket change. They cross every demographic category. As we often say, if you're going to reproduce and buy stuff -- or if you know someone who is -- you're a toy consumer. And, those consumers have more than 160,000 different toys to choose from at any time -- ranging from the hot, TV-promoted items to inexpensive impulse toys. It's also the only industry where the performance of a multi-billion, multinational company can be largely dependent on the whims of an 8- year-old.